2019
DOI: 10.1109/jphot.2019.2931306
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Crack Measurement Using Distributed Optic-Fiber Sensor Based on Raman Loop Configuration and Fiber Loss

Abstract: In recent years, optic-fiber sensors have been required to simultaneously measure the structure's crack and environmental temperature in the infrastructure monitoring system. We proposed and experimentally demonstrated a distributed optic-fiber sensor based on the Raman loop configuration and fiber loss characteristic for detecting the temperature and structure's crack. Among them, the Raman loop configuration with reference fiber is proposed to detect the temperature profile along the sensing fiber. It can el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…In this case, development of a dual-parameter detection scheme based on a single optical fiber becomes an important technical problem for Raman distributed optical fiber sensing. For the purpose of solving the above-mentioned problems, researchers have proposed a variety of advanced solutions 26 , 134 – 138 , which are as follows.…”
Section: Challenges and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this case, development of a dual-parameter detection scheme based on a single optical fiber becomes an important technical problem for Raman distributed optical fiber sensing. For the purpose of solving the above-mentioned problems, researchers have proposed a variety of advanced solutions 26 , 134 – 138 , which are as follows.…”
Section: Challenges and Methodsmentioning
confidence: 99%
“…In 2019, Li and Zhang et al demonstrated a novel dual-parameter optical fiber sensing scheme based on Stokes optical loss and the Raman effect to measure the distributed temperature and structural cracks 26 . The scheme was based on the double-end loop configuration and Stokes optical loss to extract the distributed temperature and crack information along the fiber-line.…”
Section: Challenges and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SHM is achieved by nondestructive testing methods without damaging the components being inspected, in industry, such as common visual inspection [4], ultrasonic inspection [5], eddy current inspection [6], and fiber optic inspection [7]. Visual inspection is a method by which a person periodically detects the degree of structural damage using auxiliary equipment [8], which has high labor costs, low detection efficiency, and environmental constraints.…”
Section: Introductionmentioning
confidence: 99%